Edukasi Bahaya Pewarna pada Makanan Jajanan terhadap Kesehatan Anak - Zaenab; Azizah, Nurfitriani; Rafidah, Rafidah; Haerani, Haerani (Poltekes Kemenkes Tanjungpinang, 2024)
The lack of attention from various groups to the risks of food-related issues, such as food poisoning and cancer caused by harmful food additives, particularly affects the health of elementary school-aged children. The purpose of this community service program was to increase children's knowledge and understanding through education about the dangers of food coloring in snacks at UPT SPF SDN KIP Bara-Baraya II, Makassar City. The method of implementation included lectures in the form of educational sessions, demonstrations, pre- and post-tests, and the distribution of leaflets, aimed at assessing the participants' level of knowledge. The results of the community service program showed an improvement in participants' knowledge, with 26 participants (75%) categorized as having good knowledge, 5 participants (14%) in the moderate knowledge category, and 4 participants (11%) in the poor knowledge category. The community service activity concluded that out of 35 participants, there was a significant change in their level of knowledge after receiving education on the dangers of food coloring in snacks and its effects on children's health. It is recommended that students become more selective when choosing foods to consume, particularly avoiding those containing harmful coloring substances.